Review of Georgian Leasing Market and Perspectives for Development - Orjonikidze, Nino; Nino Liparteliani (European Journal of Multidisciplinary Studies, 2017)
At contemporary stage leasing has formed as one of the dynamically growing trend that encourages investment progressions throughout the world business development. In the modern world, leasing acts as a multimillion industry. 80 percent of companies in developed countries use this financial instrument. 1/3 of investments in fixed assets are accomplished by means of leasing. Leasing companies have quite diverse business and operations. All these depend on lease term, type of relation, form of object, organizational structure of a company, etc. Leasing essentially is a whole complex of three simultaneously executed operations (lease, crediting and material support). At certain point, leasing is similar to credit, which is given to buy an object. Consequently, it may be called a property credit. Nowadays, in Georgia, banking credit is more well-known than leasing, in spite of the fact that for entrepreneurs leasing is more convenience than banking credit.
Keywords: Leasing, advantage, alternative, calculation, leasing market.